Model Islamic Corporate Governance (ICG) Wakaf Uang Berbasis Kewirausahaan: Studi Multi Kasus di Indonesia dan Malaysia - Tri Ratnasari, Ririn; Nur Indah Rofiqoh, Siti; Sukmana, Raditya; Alimin, Alimin; Sulistyowati, Sulistyowati (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2021)
This study aims to determine the Islamic Corporate Governance (ICG) model of entrepreneurship-based cash waqf. Using qualitative research methods and a multi-case study approach, research data were obtained primarily (in-depth interviews), online report documentation, journal articles, and books. Data analysis conclude that the ICG model of entrepreneurship-based cash waqf is built from a unique waqf membership model (waqf donations come from the company's Corporate Social Responsibility), determination of special donors, and determination of beneficiaries of waqf productivity funds in public facilities development programs that are integrated with entrepreneurial activities. This study recommends the issuance of entrepreneurship-based cash waqf shares, both permanent and temporary.